2020
DOI: 10.5606/tgkdc.dergisi.2020.19436
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted lobectomy versus completely portal robotic lobectomy: What is the difference?

Abstract: Background: This study aims to compare robot-assisted lobectomy versus completely portal robotic lobectomy. Methods: Between January 2014 and December 2019, a total of 41 patients (10 males, 31 females; median age 62 years; range, 50 to 68 years) underwent robotic anatomical pulmonary resection in our institution were retrospectively analyzed. The patients were consecutively divided into two groups: the first 20 (48.8%) patients underwent pulmonary resection by robot-assisted lobectomy technique, while the nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The complete-portal robotic surgical technique provides many advantages over traditional robotic thoracic surgery with a utility incision. First, CO 2 insufflation provides a better view of the surgical field, extending the endoscopic field by lowering the diaphragm and compressing the lung [ 13 , 15 , 28 ]. This is particularly important for mediastinal tumour resection in remote and narrow spaces.…”
Section: Discussionmentioning
confidence: 99%
“…The complete-portal robotic surgical technique provides many advantages over traditional robotic thoracic surgery with a utility incision. First, CO 2 insufflation provides a better view of the surgical field, extending the endoscopic field by lowering the diaphragm and compressing the lung [ 13 , 15 , 28 ]. This is particularly important for mediastinal tumour resection in remote and narrow spaces.…”
Section: Discussionmentioning
confidence: 99%
“…CPRL provides a fully enclosed thoracic operating space filled with warm CO 2 . The pressure of CO 2 can push down on the diaphragm and compress the lung parenchyma, increasing the surgeon's workplace and improving the surgical field 28 . In addition, the increased pressure in the thoracic cavity can also effectively inhibit the tissue of mild bleeding 30 .…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, the use of completely portal robotic lobectomy (CPRL) and uniportal VAL has rapidly increased. 28 , 29 Without using utility incision, CPRL and uniportal VAL allow thoracic surgeons to use CO 2 insufflation to achieve a better view of the surgical field. It has been reported that CPRL could significantly reduce intraoperative blood loss and shorten operative time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation